ANALISIS PERENCANAAN PEMBELAJARAN BERBICARA DENGAN TEKNIK ROLE PLAY PADA SISWA KELAS VIII SMPN 14 KABUPATEN SORONG - Selfiani, selfiani; Rima (FRASA: Jurnal Keilmuan, Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to analyze the planning of speaking instruction using the role-play technique for eighth-grade students at SMPN 14 Sorong Regency. The research problem is focused on four aspects: the completeness and relevance of the components of the Lesson Plan (RPP), the clarity of the speaking skill indicators, the variety of role-play scenarios, and the assessment instruments used. The research method employed is descriptive qualitative, with the subjects being the Indonesian language teacher and lesson plan documents, as well as eighth-grade students as participants. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The findings reveal that the lesson plans for speaking instruction using role play at SMPN 14 Sorong Regency are administratively complete, but the speaking skill indicators remain general and lack measurability. The role-play scenarios are limited to certain themes and thus not fully contextual, while the assessment instruments tend to emphasize linguistic aspects and do not adequately address non-linguistic aspects such as expression and intonation. The conclusion of this study is that the quality of speaking instruction planning through role play needs improvement by formulating more specific indicators, designing more varied and contextually relevant scenarios, and developing more comprehensive assessment instruments. This research contributes the concept of a “Context-Based Role Play Lesson Planning Analysis Model,” which can serve as a reference for teachers in developing more effective speaking instruction plans.